Correlation of hearing impairment with site of tympanic membrane perforation - Bhusal, C.L.; Guragain, R.P.S.; Shrivastav, R.P. (Journal of Institute of Medicine Nepal, 2007)
Objective: This prospective study was done to assess the level of preoperative hearing impairment in different sites of pars tensa perforation in patients with chronic suppurative otitis media (CSOM) tubo-tympanic type undergoing myringoplasty. Materials and Methods: A total of 50 patients were recruited from the outpatient Department of Otorhinolaryngology and Head and Neck Surgery from June 2003 to May 2004. Cases of CSOM tubo-tympanic type with dry central perforation, with conductive type of hearing loss were subjected to myringoplasty. Preoperative audiometric evaluations were done. Just prior to operation, examination under microscope was performed. Exact site of perforation was noted. During operation, those found to have ossicular discontinuity or fixation were excluded from this study. Results: It was observed that the greatest hearing loss was found in big central (45dB) and posterior central (43dB); whereas least in those of anterior central (31dB) and central malleolar (34dB) perforations. The average hearing loss at 500Hz, 1000Hz and 2000Hzwas 46.40 dB, 30.90 dB and 31.9 dB respectively. This showed that the hearing loss is maximum at the lowest frequencies and minimum as the frequencies increase. Conclusion: This study shows that the posterior-central perforations cause more hearing loss than anterior-central ones. The hearing loss is maximum at the lowest frequencies and minimum as the frequencies increase. Journal of Institute of Medicine Vol.27(2) 2005